Survival Rate of Patients with Acute Leukemia: A Case Study in Iran - Mohammad Ranjbar; Mohsen Barouni; Vahid Moazed; Hossein Fallahzadeh; Shiva Sheikholeslami (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Acute leukemia is a kind of aggressive disease that includes high rates of fatalities in the world, in particular in Iran. This research was done to determine the survival rate of patients with acute leukemia in Iran. Methods: 85 adult patients who were first diagnosed with acute leukemia in Shahid Bahonar hospital of Kerman during March 2012 until March 2013 were evaluated in a retrospective descriptive study to measure the death/life status in a 5-year period (2012-2017). The required data was gathered from medical records of patients, HIS system data, and the cancer registry system, and the Kaplan-Meier estimator and Log Rank test were used to calculate the survival rate using SPSS23. Results: Survival rate was completely 45.9 % for patients with acute adult leukemia. It was 47.08 % in acute myelogenous leukemia (AML) and it was 43.06 % in acute lymphocytic leukemia (ALL). The 1,2,3,4 and 5-year survival of acute leukemia was respectively 87.1 %, 69.4 %, 62.4 %, 56.5 % and 45.9 %. Conclusion: Iranchr('39')s health system should design and plan to increase the survival of patients with acute leukemia by improving the methods and facilities to diagnose and treat it more quickly and more effectively.